2004
DOI: 10.1016/s0002-9440(10)63325-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of LFA-1, but not Mac-1, Protects MRL/MpJ-Faslpr Mice from Autoimmune Disease

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by immune complex-mediated tissue injury. Many different adhesion molecules are thought to participate in the development of SLE; however, few studies have directly examined the contributions of these proteins. Here we demonstrate that LFA-1 plays an essential role in the development of lupus in MRL/MpJ-Fas(lpr) mice. Mice deficient in LFA-1, but not Mac-1, showed significantly increased survival, decreased anti-DNA autoantibody formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 49 publications
5
58
1
Order By: Relevance
“…Despite a dominant role for ICAM-1 and a codominant requirement for Mac-1 and LFA-1 in the cutaneous reverse Arthus reaction (36), the K/B ϫ N serum transfer model of autoantibody-induced synovial inflammation displays only partial dependence on ICAM-1 and no dependence on Mac-1 for disease induction. Indeed, the dependence on LFA-1 in the K/B ϫ N serum transfer model is more similar to that reported in the MRL/MpJ-Fas lpr immune complex-dependent model of lupus, which demonstrates attenuated nephritis with decreased renal neutrophil accumulation in LFA-1 null mice (37). These differences highlight the anatomic specificity for ␤ 2 integrins and their ligands in distinct immune complex-mediated diseases.…”
Section: Discussionsupporting
confidence: 73%
“…Despite a dominant role for ICAM-1 and a codominant requirement for Mac-1 and LFA-1 in the cutaneous reverse Arthus reaction (36), the K/B ϫ N serum transfer model of autoantibody-induced synovial inflammation displays only partial dependence on ICAM-1 and no dependence on Mac-1 for disease induction. Indeed, the dependence on LFA-1 in the K/B ϫ N serum transfer model is more similar to that reported in the MRL/MpJ-Fas lpr immune complex-dependent model of lupus, which demonstrates attenuated nephritis with decreased renal neutrophil accumulation in LFA-1 null mice (37). These differences highlight the anatomic specificity for ␤ 2 integrins and their ligands in distinct immune complex-mediated diseases.…”
Section: Discussionsupporting
confidence: 73%
“…We have recently reported that the loss of CD11b in the MRL/ MpJ-Fas lpr mouse lupus model results in enhanced lymphadenopathy with focal accumulation of plasma and Mott cells. 15 A recent study has also shown that CD11b may also govern T-cell development and function, in that the loss of CD11b decreased CD3 and CD28 expression and CD4/CD8 ratios. 60 Early reports dismissed a role for T cells in DSS colitis; however, recent reports suggest that this cell population may participate in a regulatory manner through influencing recruitment of specific leukocyte populations (ie monocytes vs granulocytes) or by providing growth factors necessary for epithelial cell survival and regeneration during DSS colitis.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14][15][16] The b 2 integrins are heterodimeric proteins that consist of a common beta subunit (CD18) noncovalently attached to different alpha subunits (CD11a-d). 17 The b 2 integrin family, or CD18 integrins, consists of four different adhesion proteins LFA-1 (CD11a/CD18), Mac-1 (CD11b/ CD18), p150/95 (CD11c/CD18), and CD11d/CD18.…”
Section: Inflammatory Bowel Diseases (Ibd) Includingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, inhibiting T cell DNA methylation with the DNA methyltransferase inhibitor 5-azacytidine increases LFA-1 overexpression. Furthermore, Kevil et al reported that in MRL/MpJ-Fas lpr mice which develop a systemic autoimmune disease with similarities to SLE, loss of LFA-1 significantly protected mice from the development of murine lupus, as measured by attenuated autoantibody formation, and inhibited development of glomerulonephritis, and increased survival compared to control MRL/MpJ-Fas Lpr mice (63). Dr Richardson's group demonstrated that regions flanking the promoter of the ITGAL gene, which encodes for the CD11a chain of LFA-1, demethylate during aging, providing evidence that age-dependent decreases in T cell DNA methylation may contribute to the changes in T cell function and gene expression that occur in aging (64).…”
Section: Cross-talk Between Epigenetics Aging and Late-life Diseasesmentioning
confidence: 99%